Influence of internal hydrogen content on the evolved microstructure beneath fatigue striations in 316L austenitic stainless steel. (July 2021) - Nygren, K.E.; Nagao, A.; Wang, S.; Sofronis, P.; Robertson, I.M.
Abstract: The effect of internal hydrogen (up to 104.2 mass ppm) on the tensile and fatigue properties of SUS316L austenitic stainless steel was investigated. Internal hydrogen had minimal impact on the tensile properties but reduced the fatigue lifetime, but not monotonically with hydrogen concentration. The evolved microstructural state beneath the fatigue fracture surface showed commonalities and differences with crack length and the presence of hydrogen. Hydrogen influenced the evolved microstructural state, resulting in the formation of smaller dislocation cells with thicker cell walls, and modified the distribution of deformation twins. The non-linear dependence of the response on fatigue lifetime with increasing hydrogen concentration was attributed to hydrogen-induced changes in the macroscopic mechanical properties at the highest concentration. As the emphasis of this paper is on relating the hydrogen-induced changes in the deformed microstructural state to those in the mechanical properties, the results are discussed in terms of the hydrogen-enhanced localized plasticity mechanism. Graphical abstract: Image, graphical abstract